Developing Ecological Flow Needs in a Highly Altered Region: Application of California Environmental Flows Framework in Southern California, USA - Taniguchi-Quan, Kristine T.; Irving, Katie; Stein, Eric D.; Poresky, Aaron; Wildman Jr, Richard A.; Aprahamian, Amanda; Rivers, Cindy; Sharp, Grant; Yarnell, Sarah M.; Feldman, Jamie R. (Frontiers in Environmental Science, 2022)
Flow alteration is a pervasive issue across highly urbanized watersheds that can impact the physical and biological condition of streams. In highly altered systems, flows may support novel ecosystems that may not have been found under natural conditions and reference-based environmental flow targets may not be relevant. Moreover, stream impairments such as altered channel morphology may make reference-based environmental flow targets less effective in supporting ecosystem functions. Here, we develop an approach for determining ecological flow needs in highly modified systems to support existing ecological uses utilizing the California Environmental Flows Framework (CEFF). CEFF was established to provide guidance on developing environmental flow recommendations across California’s diverse physical landscape and broad array of management contexts. This paper illustrates the application of CEFF in informing ecologically-based flow restoration in a highly altered region of South Orange County, California. The steps of CEFF were implemented including a stakeholder process to establish goals and provide input throughout the project; identifying the natural ranges of functional flow metrics, or distinct components of the natural flow regime that support ecosystem functions; refining ecological flow needs to account for altered channel morphology and the life history needs of riparian and fish species; and assessing flow alteration to inform management strategies. Key considerations and lessons learned are discussed in the context of developing ecological flow needs in highly altered systems including when non-flow related management actions (i.e., channel rehabilitation) are necessary to achieve ecological goals.